Longitudinal changes in Mediterranean diet and transition between different obesity phenotypes. Issue 3 (March 2020) - Konieczna, J.; Yañez, A.; Moñino, M.; Babio, N.; Toledo, E.; Martínez-González, M.A.; Sorlí, J.V.; Salas-Salvadó, J.; Estruch, R.; Ros, E.; Alonso-Gómez, A.; Schröder, H.; et al.
Summary: Background & aims: Little is known about the impact of specific dietary patterns on the development of obesity phenotypes. We aimed to determine the association of longitudinal changes in adherence to the traditional Mediterranean diet (MedDiet) with the transition between different obesity phenotypes. Methods: Data of 5801 older men and women at high cardiovascular risk from PREDIMED trial were used. Adherence to MedDiet was measured with the validated 14p-Mediterranean Diet Adherence Screener (MEDAS). Using the simultaneous combination of metabolic health- and body size-related parameters participants were categorized into one of four phenotypes: metabolically healthy and abnormal obese (MHO and MAO), metabolically healthy and abnormal non-obese (MHNO and MANO). Cox regression models with yearly repeated measures during 5-year of follow-up were built with use of Markov chain assumption. Results: Each 2-point increase in MEDAS was associated with the following transitions: in MAO participants, with a 16% (95% CI 3–31%) greater likelihood of becoming MHO; in MHO participants with a 14% (3–23%) lower risk of becoming MAO; in MHNO participants with a 18% (5–30%) lower risk of becoming MHO. In MANO women, but not in men, MEDAS was associated with 20% (5–38%) greater likely of becoming MHNO ( p for interaction by gender 0.014). No other significant associations were observed. Conclusions: Better adherence to the traditional MedDiet is associated with transitions to healthier phenotypes, promoting metabolic health improvement in MAO, MANO (only in women), and MHO, as well as protecting against obesity incidence in MHNO subjects.